Manichaeism, memoir and official history: some contributions to re-think citizenship education in Peru (Revista Peruana de Investigación Educativa, 2021)
The purpose of this paper is to theoretically and synthetically approach the linkage between memoir and history in the construction of the narratives that have influenced the school discourse about citizenship and identity in Peru, in a very peculiar and personal manner. We depart from a philosophical characterization of the concept of memoir and its relation with some moral concepts, to then introduce ourselves in a more sociological, and theoretical, discussion about the way in which history and memoir are incorporated in the educational field through tense cultural operations and, to some extent, violent; which conduct us to explore this phenomenon in the Peruvian case and in direct relation with the pedagogical intention of building citizenship. Although we do not intend to pose conclusive statements, we seek to conceive the educational space as still open enough to work in the enlargement of the margins in the comprehension process of our national identity, our conception of citizenship and what it means to be a Peruvian citizen in the XXI century.
Keywords: memoir; history; education; hegemony; citizenship